2018
DOI: 10.12740/pp/onlinefirst/79835
|View full text |Cite
|
Sign up to set email alerts
|

Mental rotation task in bipolar disorder

Abstract: Cel pracyChoroba Afektywna Dwubiegunowa (ChAD) istotnie wpływa na poziom dysfunkcji poznawczych i motorycznych. Badania nad funkcjami poznawczymi w Chorobie Afektywnej Dwubiegunowej wskazują między innymi na występowanie deficytów w zakresie przetwarzania wzrokowo – przestrzennego i pamięci wzrokowo – przestrzennej. Dotychczas w badaniach z udziałem pacjentów z ChAD nie wykorzystywano jednak Testu Rotacji Mentalnych (Mental Rotation Task) do oceny tych funkcji. Naszym celem było wprowadzenie tej metody i ocena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Our previous study showed that while BD patients show no signs of implicit sequence learning, SZ patients exhibit some features of motor learning when using the right hand, reflected by a gradual decrease in RT across all of the SRTT blocks. Both disorders share structural and functional impairments of the brain areas involved in SRTT ( 2 ), such as the prefrontal cortex ( 21 , 22 ), primary motor cortex ( 23 25 ), supplementary motor area ( 26 28 ), cerebellum ( 29 , 30 ), and striatum ( 11 , 31 , 32 ). Moreover, SZ and BD patients share motor function deficits associated with the abovementioned structures impairments, such as neurological and cerebellar soft signs ( 33 35 ), eyeblink conditioning (cerebellar learning paradigm) ( 36 , 37 ), or oculomotor deficits ( 8 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that while BD patients show no signs of implicit sequence learning, SZ patients exhibit some features of motor learning when using the right hand, reflected by a gradual decrease in RT across all of the SRTT blocks. Both disorders share structural and functional impairments of the brain areas involved in SRTT ( 2 ), such as the prefrontal cortex ( 21 , 22 ), primary motor cortex ( 23 25 ), supplementary motor area ( 26 28 ), cerebellum ( 29 , 30 ), and striatum ( 11 , 31 , 32 ). Moreover, SZ and BD patients share motor function deficits associated with the abovementioned structures impairments, such as neurological and cerebellar soft signs ( 33 35 ), eyeblink conditioning (cerebellar learning paradigm) ( 36 , 37 ), or oculomotor deficits ( 8 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, decreased visuo-spatial attention ability has been associated with ADHD symptoms [ 49 ], anxiety and aggression [ 50 , 51 , 52 ], depression [ 53 , 54 ], and manic depression [ 55 ]. People with ADHD [ 56 ], anxiety [ 57 ], depression [ 58 , 59 ], aggression [ 60 ], and manic depression [ 61 ] showed declined mental rotation abilities.…”
Section: Methodsmentioning
confidence: 99%